СОЦІАЛЬНО-ЕКОНОМІЧНІ ФАКТОРИ ОСОБИСТОГО СПОЖИВАННЯ, ЯК ЧАСТИНА ПРОДОВОЛЬЧОЇ БЕЗПЕКИ (International Journal of Innovative Technologies in Economy, 2018)
The article defines food security, as well as some socio-cultural aspects of food consumption. The level of health of the population is determined depending on the national-regional peculiarities. The problem of quality and safety of products, in particular meat processing enterprises, is considered. Some weaknesses of this branch are highlighted, and the essence of a balanced diet of a personality is given. The analysis of trade in food products in recent years has been carried out, and the forecast of world meat production has been provided.